The Impact of Academic Stress on Psychological Well-Being with Life-College Balance as a Moderating Variable for Students in Jakarta - Kuswanto, Hary (CV. Publikasi Indonesia, 2025)
Academic stress can affect a student's psychological well-being, but college-life balance can play a role in mitigating the impact. This study aims to analyze the influence of academic stress on the psychological well-being of students in Jakarta, by considering the life-college balance as a moderation variable. A quantitative approach with a cross-sectional design was used in this study, which involved 300 students in Jakarta. Data were obtained through questionnaires that measured academic stress (using the Academic Stress Scale / ASS), Work-Life Balance Scale (WLBS), and psychological well-being (Ryff's Psychological Well-Being Scale / RPWBS). Multiple linear regression analysis was applied to test the relationship between variables. The results showed a negative relationship between academic stress and students' psychological well-being, which was consistent with previous research. In addition, college-life balance was shown to moderate the effects of academic stress, where students who had a better college-life balance experienced a lower negative impact on their psychological well-being. These findings have significant implications for higher education policy, which needs to provide support programs to help students manage academic stress and improve their college-life balance. This research also opens up space for further research on other factors that can affect the psychological well-being of students.